Perancangan Sistem Pemesanan Makanan Berbasis Web menggunakan PHP dan MySQL: Budi Kurniawan, Muhammad Romzi (Universitas Mahakarya Asia, 2021)
Information sistems are currently widely used to optimize a conventional sistem to make it even better. Currently, Ummi Yuli's restaurant still uses a conventional ordering sistem where customers order food by filling in the purchase note with paper and looking at the food menu from the available menu list then handing it over to the receptionist where there are many deficiencies of the sistem currently used for both consumers and owners. This research was conducted to create a simple food ordering information sistem using a website that contains all data about ordering food, drinks, order status and payment to the cashier. The method used is RAD (Rapid Application Development) or rapid prototyping, which is a software development process model that is classified as an incremental technique (multilevel) with an emphasis on short, short, and fast development cycles. With this sistem, it is hoped that it will make the food ordering sistem better and more effective and efficient Reference Bekti, Bintu Humairah. 2015. Mahir Membuat Website dengan Adobe Dreamweaver CS6, CSS dan JQuery. Andi. Yogyakarta Jubilee Enterprise. 2010. Panduan Memilih Koneksi Internet untuk Pemula, PT Elex Media Komputindo. Jakarta Jogiyanto, H.M., 2005, Analisa dan Desain Sistem Informasi: Pendekatan Terstruktur Teori dan Praktik Aplikasi Bisnis, ANDI, Yogyakarta Kadir, Abdul. 2014. Pengenalan Sistem Informasi Edisi Revisi. Andi. Jogjakarta Reni Rosmitalia. 2016. Sistem Pemesanan Makanan di Rumah Makan Palapa Indah berbasis Web Service Menggunakan Mobile Android. Univ Islam Negeri Raden Fatah. Palembang Tim EMS, All in One Web Programming (Jakarta : PT Elex Media Komputindo, 2016) https://bitlabs.id/blog/rad-adalah/ (Diakses 27 Mei 2021) Author Biography Budi Kurniawan, Universitas Mahakarya Asia S1 Teknik Informatika Universitas Amikom Jogjakarta S2 Teknik Informatika Universitas Bina Darma Palembang